Corporate Governance Regimes and Employment Relations in Europe - Goergen, Marc; Brewster, Chris; Wood, Geoffrey (Relations industrielles / Industrial Relations, 2009)
SummaryAn influential strand of the finance literature focuses on the nature and extent of shareholder rights vis-à-vis employees. Most of the extant literature on the subject relies on a limited number of case studies and/or broad macroeconomic data, whereas this article draws on evidence from a large scale survey of organizations to test the predictions of the theories on the relative strength of workers and managers across the different governance regimes. This evidence highlights the complex relationship between societal institutions, legal traditions, political parties and electoral systems, on corporate governance regimes and the relative strength of unions and collective representation at workplace level, highlighting the limitations of the mainstream finance and economics rational-incentive based literature, and the value of alternative socio-economic approaches.